KONTRIBUSI POWER LENGAN DAN POWER TUNGKAI TERHADAP KEMAMPUAN RENANG GAYA BEBAS PADA ATLET GARUDA LAUT MAKASSAR - Andi Nahdia T Walinga; M Adam Mappaompo; Hasnah Hasnah; Andi Anwar Ishar (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2023)
The population of this study was the Makassar sea eagle swimming athlete. Using purposive-sampling in taking samples and the test instruments used: 1) Medicine Ball Push, 2) vertical jump, 3) stopwatch to measure speed. The variables of this study include power and speed in freestyle swimming. Data analysis techniques using regression and correlation tests with a significance of 95% (α = 0.05). Based on the results of the analysis of the data this study shows that: (1) there is a significant effect of arm power on the ability to swim freestyle in Makassar sea eagle athletes with a contribution of 38.8% (2) there is a significant effect of leg power on the ability to swim freestyle in Makassar sea eagle athletes seen from the contribution of 60.4% (3) there is a significant influence of arm power and leg power together on the ability to swim freestyle in Makassar sea eagle athletes seen from the contribution of 61.4%.